Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
5x∛69 = 6x√59
Subtract 6x√59 from each side:
5x∛69 - 6x√59 = 0
Factor the left side:
x (5∛69 - 6√59) = 0
Divide each side by (5∛69 - 6√59) :
x = 0
Subtract 6x√59 from each side:
5x∛69 - 6x√59 = 0
Factor the left side:
x (5∛69 - 6√59) = 0
Divide each side by (5∛69 - 6√59) :
x = 0
[tex]5x \sqrt[3]{69}=6x \sqrt{59}\ \ \ \Leftrightarrow\ \ \ 5x \sqrt[3]{69}-6x \sqrt{59}=0\\\\x(5 \sqrt[3]{69}-6 \sqrt{59})=0\ \ \ \Leftrightarrow\ \ \ x=0[/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.